Building a robust 3D Ca-MOF by a new square Ca4O SBU for purification of natural gas. Issue 26 (16th June 2020) - Hu, Falu; Di, Zhengyi; Wu, Mingyan; Li, Jing
Abstract : For the first time, a new square Ca4 O SBU is introduced into a 3D Ca-MOF, ([MeNH2 ]2 [Ca4 O(MTB)2 (EtOH)4 ])·(solvent)n (1), to generate a structure with (4, 8)-connected flu-topology, which shows good selectivity of CO2, C2 and C3 hydrocarbons over CH4 . Abstract : For the first time, a new square Ca4 O SBU is introduced into a 3D Ca-MOF, ([MeNH2 ]2 [Ca4 O(MTB)2 (EtOH)4 ])·(solvent) n (1 ), to generate a (4, 8)-connected flu -topology structure. Compound 1 exhibits selective adsorption of C3 and C2 hydrocarbons and CO2 over CH4 with especially high IAST selectivities for C3 hydrocarbons over CH4 (at 15/85 and 50/50 ratio) at 298K and 1 bar.